Effects of Ni and Cr on the high-temperature oxidation behavior and mechanisms of Co- and CoNi-base superalloys. (December 2022) - Li, Longjun; Wang, Li; Liang, Zhida; He, Junyang; Qiu, Jingwen; Pyczak, Florian; Song, Min
Graphical abstract: Highlights: Fine oxide particles in the intermediate layer were characterized by TEM and STEM. 30 at.% Ni can relieve oxide layer spallation and reduce void formation in the oxide scales. Cr promotes continuous Al2 O3 layer formation and reduces the oxide scale thickness. Ni and Cr have different effects on the chemical activity of alloying elements. Abstract: The high-temperature oxidation behaviors of Co- and CoNi-base alloys with different Ni and Cr additions were investigated by isothermal oxidation in air at 900 and 1000 °C. The structure, composition, and element distribution in the three layers within the oxide scales in different alloys have been explored in detail by electron microscopy, especially with regard to the fine oxide particles in the intermediate layer. Based on the microstructure and phase constitution of the oxide scales, the synergetic effects of alloying elements on the oxidation mechanisms and resistance have been elucidated in detail with the aid of CALPHAD calculation.